Online Social Networking among students and its impact on Marketing - The Case of YouTube - Sahgal, Shaira (2008)
ABSTRACT The literature on online social networking and the use of the internet for socialising purposes by adolescents and youngsters today is fairly recent and there does not seem to be much existing research on the topic barring the few. This study aims to try and fill that gap through interviews conducted among university students and understanding the reasons behind their preference for such online means of communicating and broadcasting as opposed to traditional offline methods like the telephone. With the use of semi-structured interviews, the researcher has addressed various aspects of the use of online social networks in the form of research questions that include 1. reasons for their preferences of online social networks vs. traditional methods to communicate, 2. Their frequency of use and the kinds of videos and content they access on YouTube, 3. Whether they share videos with friends and how actively do they use the different components of YouTube, 4. Their views on the matter of privacy on the internet, 5. Pros and cons they perceive in the excessive use of such sites by students and finally, the use of such sites in the world of marketing and advertising today and in the future. The findings of this research have interesting and significant implications, specifically for marketers and marketing professionals today.